EMPOWERMENT OF FARMER GROUPS THROUGH AGRICULTURAL FINANCIAL MANAGEMENT TRAINING: OPTIMIZING FARMER EXPENDITURES AND INCOME IN THE AMONG TANI FARMER GROUP - Subagyo Subagyo; Dwi Wulandari; Afwan Hariri Agus Prohimi; Buyung Adi Dharma; Ari Gunawan; Afis Baghiz Syafruddin (Dharmas Education Journal (DE_Journal), 2024)
Effective financial management is essential to the sustainability of farming businesses, especially amid economic changes and challenges faced by farmer groups such as Among Tani in Bumiaji, Batu City. Despite the growing awareness of the importance of financial management, many farmers still have difficulty applying the correct financial principles, especially in separating personal finance and farming. This creates a significant knowledge gap in applying practical and efficient financial management among farmers. Financial management training is carried out using a practical approach to answer this need, where the material is delivered through a combination of theory and practical sessions directly in the field. The main results of this training show that there is an increase in farmers' knowledge and skills in recording financial transactions, budgeting, and financial risk management. The participant's response was also very positive, with high enthusiasm for applying the techniques learned, and planned to form a small group focusing on joint financial management. Some participants even expressed their intention to immediately implement more transparent and efficient recording techniques in their farming businesses. The implications of this activity show that this kind of training is not only able to improve the technical skills of farmers but also change their mindset about the importance of sustainable financial management, which is ultimately expected to strengthen the financial independence of the farmer group as a whole.